Plasma NT‐proBNP and Cell‐Free DNA Concentrations after Prolonged Strenuous Exercise in Working Farm Dogs. (2nd December 2017) - Hunt, H.; Cave, N.; Bridges, J.; Gedye, K.; Hill, K.
Abstract : Background: Plasma N‐terminal pro–B‐type natriuretic peptide (NT‐proBNP) concentration is increased in dogs with myocardial dysfunction, and cell‐free DNA (cfDNA) increases in numerous disease states. In humans, both of these biomarkers can be altered after endurance exercise. Objective: To investigate the effect of prolonged strenuous exercise on circulating NT‐proBNP and cfDNA concentrations in working farm dogs. Animals: Six healthy, privately owned working farm dogs (4 Huntaways and 2 heading dogs) from the same hill country farm in New Zealand. Methods: Prospective, nonrandomised cohort study. Venous blood samples were collected before and after the dogs worked over 4 days. Plasma NT‐proBNP concentrations were measured by a commercially available ELISA assay and cfDNA concentrations were determined by fluorometry without prior DNA extraction. Results: The baseline (before work, Day 1) median plasma NT‐proBNP concentration was 664 pmol/L. A linear mixed‐effects model showed that work increased plasma NT‐proBNP concentrations by 101 ± 9% ( P < 0.001), but with each consecutive day of work, NT‐proBNP concentrations declined by 16 ± 4% ( P < 0.001). The baseline median plasma cfDNA concentration was 653 ng/mL, and plasma cfDNA concentrations increased by 138 ± 45 ng/mL after work ( P = 0.004). Conclusions and Clinical Importance: The plasma concentration of NT‐proBNP in healthy Huntaways and heading dogs after work can exceed the upper limit of the reference range. Results in dogs sampled on the day of prolonged strenuous exercise should be interpreted with caution. Plasma concentrations of cfDNA also increase with exercise, but further studies are needed to establish reference ranges in healthy dogs.